The effectiveness of rectangular block as energy dissipation structure - Adam, Ismail (2015)
Velocity of flow water in a channel will increase when there are different between water level at upstream and downstream of a channel. High velocity of flow water can be possessed by water flow in a spillway which the flow is caused by the gravitational force. High water flow velocity can caused bad impacts such as erosion, scour, sedimentation and cavitations around spillway toe, weir bed and downstream of river. In order to overcome these problems, the flow velocity has to be reduced. This can be done through constructing an energy dissipating structure at the affected areas. Therefore, a rectangular open channel model structure consists of spillway part is constructed and used to conduct an experiment to study the performances and effectiveness of rectangular concrete block as a energy dissipation structure. The blocks used in this study have different size and different slope of spillway. The blocks are arranged in various pattern of arrangements in stilling basin of a channel. For blocks size 30 x 25 x 23 mm with slope 27 0 , the best pattern with a highest percentages reduction in velocity is pattern 5. For blocks size 30 x 30 x 30 mm with slope 27 0 , the best pattern with a highest percentages reduction in velocity is pattern 5. Based from the result, its shows that the decrease of slope will be increase the percentage reduction in velocity.